1995
DOI: 10.1095/biolreprod52.6.1389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relaxin administration in early gestation or prior to mating on uterine length and fetal survival in gilts

Abstract: The objective of this research was to determine the effect of administration of porcine relaxin to gilts during early gestation, or during the follicular phase of the estrous cycle immediately preceding mating, on the length of the uterus and consequently the number of surviving fetuses. Experiment 1 determined the individual and combined effects of 10 days of administration of relaxin (0.5 mg, 4 times daily), estradiol benzoate (1 mg, 2 times daily), and progesterone (50 mg, 2 times daily) on uterine wet weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…Similar relationships were described for the pig (Hall et al 1990, Galvin et al 1991, Ohleth et al 1997. Additionally, data generated in ovariectomized, pubertal gilts (Zaleski et al 1995) indicating that ten days of relaxin treatment failed to promote uterine growth in the absence of ovarian steroids (estrogen or progesterone), support the view that uterotrophic actions of relaxin are at least facilitated by steroid hormone receptor Uterotrophic effects of relaxin are estrogen receptor-dependent 947 activation. Studies involving the MCF-7 breast cancer cell line showed that relaxin could stimulate expression of an estrogen response element-luciferase reporter gene (Koos & Pillai 2001), indicating that signaling pathways affected by relaxin can also activate the ER in the absence of estrogen.…”
Section: Discussionsupporting
confidence: 68%
“…Similar relationships were described for the pig (Hall et al 1990, Galvin et al 1991, Ohleth et al 1997. Additionally, data generated in ovariectomized, pubertal gilts (Zaleski et al 1995) indicating that ten days of relaxin treatment failed to promote uterine growth in the absence of ovarian steroids (estrogen or progesterone), support the view that uterotrophic actions of relaxin are at least facilitated by steroid hormone receptor Uterotrophic effects of relaxin are estrogen receptor-dependent 947 activation. Studies involving the MCF-7 breast cancer cell line showed that relaxin could stimulate expression of an estrogen response element-luciferase reporter gene (Koos & Pillai 2001), indicating that signaling pathways affected by relaxin can also activate the ER in the absence of estrogen.…”
Section: Discussionsupporting
confidence: 68%
“…In nonpregnant rats, the effect of relaxin on the growth and development of the uterus is associated with vascular dilatation (547) and in rhesus and marmoset monkeys with endometrial angiogenesis (145,185). In primates and rats, pretreatment with estrogens enhances the effects of relaxin (1,145), and in pigs, estrogens are obligatory for the growth-promoting effects of relaxin (242,581). The mechanism involved in the interaction between relaxin and estrogen is not well understood, although in rats estrogen pretreatment dramatically increases relaxin receptor binding sites in the uterus (400,401,515).…”
Section: Reproductive Physiology In the Femalementioning
confidence: 99%
“…Η ρελαξίνη επηρεάζει τη συσταλτικότητα της μήτρας [482] και την ανάπτυξη της μήτρας [483] κατά τη διάρκεια της κύησης στους μύες, τους επίμυες το ινδικό χοιρίδιο και τους χοίρους, αλλά έχει μικρή επίδραση στην ανθρώπινη μήτρα [484,485] . Σε επίμυες που δεν βρίσκονται σε κύηση, η ρελαξίνη επηρεάζει τη, ανάπτυξη της μήτρας μέσω της αγγειοδιαστολής [486] και τόσο στους επίμυες, όσο και στους χοίρους και σε πρωτεύοντα ζώα, η δράση της ενισχύεται από την παρουσία οιστρογόνων [487][488][489][490] , αν και οι μηχανισμοί αλληλεπίδρασης της ρελαξίνης με τα οιστρογόνα δεν είναι καλά κατανοητοί. Η δράση αυτή της ρελαξίνης στη μήτρα δεν φαίνεται να είναι σημαντική για άλλα ζώα εκτός από τον χοίρο [491] , ενώ στον άνθρωπο πιθανότατα επηρεάζει μόνο τη διαδικασία της εμφύτευσης του ζυγώτη και όχι τα επόμενα στάδια της κύησης.…”
Section: ο φυσιολογικός ρόλος της ενεργοποίησης του Rfxp1 από την ρελαξίνηunclassified